1994
DOI: 10.1037/0882-7974.9.1.134
|View full text |Cite
|
Sign up to set email alerts
|

When expertise reduces age differences in performance.

Abstract: The authors examined whether aviation expertise reduces age differences in a laboratory task that was similar to routine air traffic control (ATC) communication. In Experiment 1, older and younger pilots and nonpilots read typical ATC messages (e.g., commands to change aircraft heading). After each message, they read back (repeated) the commands, which is a routine ATC procedure requiring short-term memory. Ss also performed less domain-relevant tasks. Expertise eliminated age differences in repeating heading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
104
6

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(120 citation statements)
references
References 30 publications
10
104
6
Order By: Relevance
“…Previous research on aging, expertise, and memory has shown that expertise can facilitate memory performance for domainrelevant information (see Krampe & Charness, 2006, for a review). This has been demonstrated in domains such as memory for chess (Charness, 1981), cooking information (Miller, 2003), aviation information (Morrow, Leirer, Altieri, & Fitzsimmons, 1994), spatial layouts (Hess & Slaughter, 1990), and music (Meinz & Salthouse, 1998), although in many cases expertise simply leads to similar benefits in performance for both younger and older adults (see Arbuckle, Cooney, Milne, & Melchior, 1994). However, given that younger and older adults likely have diVerent goals, it may not be useful to determine when both age groups reach a similar level of performance (e.g., older adults might be satisfied with any expertise-related improvements, even if they do not reach the same levels of younger adults).…”
Section: A Brain Mechanisms Value Memory and Agingmentioning
confidence: 99%
“…Previous research on aging, expertise, and memory has shown that expertise can facilitate memory performance for domainrelevant information (see Krampe & Charness, 2006, for a review). This has been demonstrated in domains such as memory for chess (Charness, 1981), cooking information (Miller, 2003), aviation information (Morrow, Leirer, Altieri, & Fitzsimmons, 1994), spatial layouts (Hess & Slaughter, 1990), and music (Meinz & Salthouse, 1998), although in many cases expertise simply leads to similar benefits in performance for both younger and older adults (see Arbuckle, Cooney, Milne, & Melchior, 1994). However, given that younger and older adults likely have diVerent goals, it may not be useful to determine when both age groups reach a similar level of performance (e.g., older adults might be satisfied with any expertise-related improvements, even if they do not reach the same levels of younger adults).…”
Section: A Brain Mechanisms Value Memory and Agingmentioning
confidence: 99%
“…As demonstrated in studies by Morrow and colleagues, when information was auditorially presented and there was no opportunity to take notes, expertise did not reduce age differences in aviation communication read-back performance. In addition to showing that note taking determined when expertise mitigated age differences, Morrow et al (1994) showed that communication task factors-such as speed of presentation, mode of presentation, and the complexity of information-either alone or in combination, affected the extent of expertise-based mitigation. For example, slower, written presentation of ATC messages concerning four-leg routes through the air space led to complete elimination of age differences among pilots in the accuracy of reading back heading commands.…”
Section: Aviation Expertise As Moderator Of Age Differences In Aviatimentioning
confidence: 99%
“…In considering past inconsistent results, Morrow et al (1994) stressed that task-domain relevance is a crucial factor determining "when expertise reduces age differences" (p. 134). More specifically, investigators need to use tasks in which the stimuli are familiar and organized and the responses are compatible with the goals of the relevant performance domain (Vicente, 1992;Vicente & Wang, 1998).…”
Section: Aviation Expertise As Moderator Of Age Differences In Aviatimentioning
confidence: 99%
See 2 more Smart Citations